Integrated transcriptomic and proteomic analyses identify the TLR2–CXCR4 axis as a regulator of endothelial cell migration under simulated microgravity - Qin, Xiaodong; Wang, Ruonan; Li, Chengfei; Pan, Yikai; Wang, Yuan; Sun, Xiqing (Frontiers in Physiology, 2025)
Simulated microgravity profoundly alters endothelial function, particularly cell migration. However, the mechanosensitive molecular pathways involved remain incompletely understood. In this study, we performed integrated transcriptomic and proteomic analyses of human umbilical vein endothelial cells exposed to simulated microgravity to identify key regulators of endothelial migration. RNA-seq and proteomic profiling identified 964 differentially expressed genes and 183 differentially expressed proteins, primarily enriched in stress response, signal transduction, and angiogenesis pathways. Combined analysis of both datasets revealed four key genes—TLR2, HSPB1, RBM3, and HSPA1B—with more than a twofold change. Protein–protein interaction analysis incorporating 48 endothelial migration—related genes further highlighted TLR2 as a central hub with strong interaction with CXCR4. Functional experiments demonstrated that simulated microgravity significantly enhanced endothelial migration through TLR2 upregulation, while TLR2 activation further promoted this response by increasing CXCR4 expression. These findings identify the TLR2–CXCR4 axis as a previously unrecognized mechanosensitive signaling pathway driving endothelial adaptation to simulated microgravity, offering potential molecular targets for therapeutic intervention against microgravity-induced vascular remodeling.